Households’ vulnerability to poverty in ibadan metropolis, oyo state, nigeria (2010)
This paper empirically assessed vulnerability to poverty at the household level using a two-period panel data set obtained from 150 households sampled from two local government areas within Ibadan Metropolis. Data were analysed using descriptive statistics, poverty indices and probit regression analysis. Analysis of the socio-economic characteristics and their relationship with vulnerability to poverty revealed that large-sized households headed by men who were old, widowed, self-employed, uneducated or who had only primary school education and no access to any form of credit, were more vulnerable than other households. The estimated probit regression model showed that marital status and tertiary education status of respondents reduced vulnerability to poverty while primary education status and household size enhanced households vulnerability to poverty.